Potongan Pelunasan Dalam Akad Murabahah Di Lembaga Keuangan Syari’ah - Sudianto Sudianto; Hadinah Mardianah (JOURNAL OF SHARIA ECONOMICS, 2025)
This study sought to ascertain how the BPRS Bhakti Sumekar Branch Pragaan should implement Fatwa No. 23/DSN-MUI/III/2002 on the termination of the Murabaha contract. The researchers employed a case study, a descriptive qualitative research method, to learn more (Case Study). The findings demonstrated that clients at the BPRS Bhakti Sumekar Pragaan Branch who choose to settle their debts ahead of schedule can do so with ease thanks to the payback deduction included in the Murabaha contract. There are two different forms of financing: payroll cut financing, which deducts 25% of the residual margin, and direct pay financing, which deducts margin decrease. The bank and the client benefit from the profit factor that is obtained.